HANDICRAFTS AND SOUVENIRS AS COMPONENTS OF THE LOCAL PRODUCTION, RETAIL AND HOSPITALITY MARKETS - DEMYDCHUK, Lyudmila (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the problems of the market of handicrafts and souvenir products, since very little attention was paid to these local markets during the study of the market economy. Despite the fact that these markets have one of the decisive values in bringing goods and services of global and national markets to the final consumer - their research has been leveled in the solution of purely regional problems. At the same time, local markets solve the vast majority of problems that are closely related to the satisfaction of everyday human needs.The relevance of the problem of local markets lies in the fact that very little attention has been paid to local markets during the entire period of market economy research. In the Carpathian region of Western Ukraine, due to many circumstances and the specifics of the geographical natural environment, a specific way of life and methods of household management were formed over the centuries, an essentially unique culture and artistic traditions were preserved, which were embodied in the development of folk arts and crafts.In Ukraine, folk arts and crafts are an integral part of national culture, which has absorbed the characteristics of individual ethnographic regions. They create a peculiar specificity in the tourism industry, in particular, such a type as industrial tourism. A characteristic feature of industrial tourism of folk crafts is the need to create a systematized list (cadastre) of its objects, which is necessary for the development of a tourist passport of the route. The products of folk arts and crafts of the region can be used to create brands of the territory, which will have a positive effect on the image of the region in general, that is, in essence, it is a local product (product), which is made from local (mostly natural) materials mainly by hand and is sold, as a rule, on territory of a defined geographical region.
Keywords: local consumer market; local consumer goods; product of folk artistic crafts; souvenir; souvenir products